2006
DOI: 10.1007/s11916-006-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of chronic pain

Abstract: The experience of chronic pain can be associated with significant distress and disability; however, this is not always the case. Although attempts to control or reduce pain can be helpful for many pain sufferers, on some occasions this is not an effective option and a different response is required. This different response can include a flexible mix of control and acceptance. The acceptance part of this mix entails a willingness to have pain, or other uncomfortable private experiences, without taking action to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 26 publications
9
72
1
Order By: Relevance
“…They are also consistent with numerous other studies of acceptance of pain, including experimental studies (e.g., Keogh, Bond, Hanmer, & Tilston, 2005;Masedo & Esteve, 2007), clinical studies (see McCracken & Vowles, 2006), and treatment outcome studies McCracken, MacKichan, & Eccleston, 2007). It has been reliably demonstrated that behavior patterns including acceptance of pain and values-based action correlate positively with emotional, physical, and social functioning in chronic pain.…”
Section: Discussionsupporting
confidence: 85%
“…They are also consistent with numerous other studies of acceptance of pain, including experimental studies (e.g., Keogh, Bond, Hanmer, & Tilston, 2005;Masedo & Esteve, 2007), clinical studies (see McCracken & Vowles, 2006), and treatment outcome studies McCracken, MacKichan, & Eccleston, 2007). It has been reliably demonstrated that behavior patterns including acceptance of pain and values-based action correlate positively with emotional, physical, and social functioning in chronic pain.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the investigation of factors that predict positive, rather than negative, adjustment are more likely to bolster patients' coping and may prove to be more effective in guiding psychosocial interventions (Dunn & Dougherty, 2005). In relation to adjustment to chronic pain, self-efficacy and acceptance have been consistently identified as two of the most important psychological factors in predicting positive coping (Buckelew et al, 1994;Jensen, Moore, Bockow, Ehde, & Engel, 2011;Keefe et al, 2004;Kratz, Davis, & Zautra, 2007;McCracken & Vowles, 2006;McCracken, Carson, Eccleston, & Keefe, 2004;Rodero et al, 2011;Van Liew, Brown, Cronan, Bigatti, & Kothari, 2013).…”
Section: Fibromyalgiamentioning
confidence: 99%
“…Pain acceptance involves a willingness to experience pain without attempting to control it, and an engagement in valued life activities, such as physical activity. 74,75 Gyurcsik and colleagues 76 found that women with arthritis who reported more pain acceptance also had higher self-regulatory efficacy beliefs to cope with arthritis-specific barriers, expected more positive arthritis-related outcomes from activity (e.g., less pain, soreness, and stiffness), had lower pain intensity, and engaged in more physical activity than their counterparts with lower pain acceptance.…”
Section: The Relationship Of Balance and Walking Limitations To Incrementioning
confidence: 99%